EXPERIMENTAL INFECTION OF ARCHANOBACTERIUM PYOGENES IN ONE DAY OLD CHICKS - M.Y. Al-attar; Mohammad A. Hamad; A. M. Al-Aalim (Basrah Journal of Veterinary Research)
The present work aimed to study the pathogenicity of Archanobacterium pyogenes by using one day old chicks and chicken Embryonated eggs .The chicks were given the bacteria(4.2x108 CFU/ml) by orally administration and intrapertoneal injection, while the Embryonated eggs inoculated into allontoic sac at 12 days of incubation. The chicks were show dullness, decrease in food intake and nervous sings, most chicks were died after 2-3 days, and the bacteria were re-isolated from internal organs, and yolk sac. The inoculation of Embryonated chicken eggs resulting in embryonicdeath, reduce hatchery percentage and deformity of embryo. The study showed that A. pyogenesisvirulence to both chicken Embryonated eggs and one day old chicks.